2012
DOI: 10.1590/s0102-695x2012005000003
|View full text |Cite
|
Sign up to set email alerts
|

Antiherpetic activity of a flavonoid fraction from Ocotea notata leaves

Abstract: This study describes the isolation of a flavonoid fraction from leaves of Ocotea notata (Nees & Mart.) [10]) present in the fraction and its activity against the Herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2). The 50% effective concentrations values (EC50) calculated from the dose-response curve and the selectivity indices (SI) against the virus were: EC50 35.8 µg/mL and SI 5.5 to HSV-1 and EC50 23.5 µg/mL and SI 8.5 to HSV-2. The flavonoid fraction was more active against HSV-2 than HSV-1. The mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 45 publications
2
20
0
3
Order By: Relevance
“…The 50% cytotoxic concentration (CC 50 ) was calculated as the dilution that caused a reduction of 50% in the number of viable cells (Vanderlei et al, 2016). The antiviral effect of Cc-SP1 and acyclovir was evaluated by the titer reduction (Garrett et al, 2012). The virus titers were calculated using the Reed and Muench statistical method and expressed as 50% tissue culture infective dose (TCID 50 ) per mL.…”
Section: In Vitro Cytotoxicity and Antiviral Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The 50% cytotoxic concentration (CC 50 ) was calculated as the dilution that caused a reduction of 50% in the number of viable cells (Vanderlei et al, 2016). The antiviral effect of Cc-SP1 and acyclovir was evaluated by the titer reduction (Garrett et al, 2012). The virus titers were calculated using the Reed and Muench statistical method and expressed as 50% tissue culture infective dose (TCID 50 ) per mL.…”
Section: In Vitro Cytotoxicity and Antiviral Assaysmentioning
confidence: 99%
“…No in situ cytotoxic effects on cell viability were detected with Cc-SP1 at CC 50 up to 1000 μg mL -1 for cultured cells, suggesting biocompatibility in vitro (Vanderlei et al, 2016). In addition, no microscopically visible change of normal cellular morphology was observed after the use of neutral red for distinguishing living, dead or damaged cells (Garrett et al, 2012, Gomaa & Elshoubaky, 2016, Vanderlei et al, 2016. Acyclovir did not exhibit cytotoxicity up to 200 μg mL -1 .…”
Section: Cc-sp1 Reveals Physical and Chemical Characteristics Of Ulvanmentioning
confidence: 99%
“…Os resultados mostraram um padrão de fragmentação característico para as duas substâncias, com perda das unidades de açúcar (m/z 609/301 e m/z 463/301) e a fragmentação das respectivas agliconas gerando o íon 1,2 A -(m/z 301/179), ambas em concordância com a literatura [37][38][39][40][41][42][43] (Material suplementar).…”
Section: Detecção De Flavonoides Por Ccd Clae-dad E Ies-emunclassified
“…However, taxifolin showed an inhibitory effect on hepatitis A virus replication in vitro, while astilbin and isoastilbin do not have antiviral properties described yet (Biziagos et al, 1987). Quercetrin is also known as bioactive phytochemical for presenting some inhibitory effects (Almeida et al, 1998;Garrett et al, 2012;Chiow et al, 2016). Almeida, et al (1998) found varied degrees of this activity using Persea americana extracts and fractions against SuHV-1.…”
Section: Antiviral Activitymentioning
confidence: 99%